The Application of Marigold Flower and Pintoi Peanuts on The Natural Enemies of Rice Plant at Antirogo Sub-District Jember Regency - Erdiansyah, Iqbal; Damanhuri, Damanhuri; Kusuma Ningrum, Dwi Rahmawati (El-Hayah : Jurnal Biologi, 2019)
The objective of the research concerning the application of Marigold flower and Pintoi peanuts of the natural enemies on Rice plant is to find out the role of refugia. This research was conducted at Antirogo Village, Sumbersari Sub-District, Jember Regency for 5 months. The research started in November 2017 to March 2018. This research wasÂ  conducted by using three squares of research area, sized 50 m2. The Treatment were, the first square employed marigold flower as the refugia. The second square used pintoi peanut as the refugia, while the third square was left without any refugia. The data of this research was analyzed statistically by using the t test. The result of this research revealed that through the utilization of marigold flower and pintoi peanut towards the natural enemies of the rice plant, it was founded out that the highest population of the vegetative phase seen on the square where the rice plant is given the pintoi peanut refugia, numbering 92. Meanwhile, the square which utilizes marigold flower showsed the number 50 unit as opposed to the finding which demonstrates that the square of rice plant without refugia showsed the number of natural enemies of 39 unit. The application of marigold flower and pintoi peanuts as the refugia playeds siginificant effect to the population of the natural enemies, respectively.